(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
This study, discuss the stability problem of Resha generation plant. The length of the transmission line which connect Resha with Haranah station, decrease the power transferred capacity that increase the risk of transient disturbance on the system, especially when the generators loaded at full load. Beside that several solutions were suggest in order to improve system stability and raise the capacity of transmitted power.